Efforts To Improve Learning Outcomes With The Demonstration Method in Grade 2 Elementary School Students - Apriyanti i Dwi Susanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study is to improve mathematics learning outcomes on the subject of place value hundreds, tens and units in learning mathematics for second grade students at SD N 02 Jatisobo Jatipuro Karanganyar odd semester of the 2021/2022 academic year with the Demonstration method and the use of number board media.  The form of this research is Classroom Action Research (CAR). This study applies the Demonstration Method and media board numbers for the discussion of place values for hundreds, tens and units in learning mathematics for second grade students at SD N 02 Jatisobo Jatipuro Karanganyar odd semester of the 2021/2022 school year. This research was conducted in two cycles, namely cycle I and cycle II. The result of this study is that the percentage of students who complete the pre-cycle is 35.71% with a class average of 63.57. While the percentage of students who complete in cycle I is 64.29% with a class average of 74.29 and the percentage of students who complete in cycle II is 100% ≥ 80% or a set performance indicator. So that the indicators were achieved in the research which was carried out in two cycles, namely cycle I and cycle II.  In this study, the application of the Demonstration Method with Number Board Media can improve mathematics learning outcomes on the subject of place value hundreds, tens and units of class II students at SD N 02 Jatisobo Jatipuro Karanganyar odd semester 2021/2022 Academic Year.